Evaluation of the state of medical care in patients with arterial hypertension in combination with gout by retrospective analysis data. - A. P. Kuzmina; O. M. Lazarenko (Medičnì Perspektivi)
The prevalence of cardiovascular diseases, especially arterial hypertension, continues to increase. An important problem is the management of the patient with a comorbid pathology in the primary link by the family physician. The purpose of this study was to assess the state of medical care in patients with arterial hypertension combined with gout, using a retrospective analysis of ambulatory cards, diagnostic and treatment data. There were analyzed 105 outpatient cards that met the inclusion criteria. The mean age of patients was 53.5±10.2 years. Among the examined patients there were 99 males (94.3%), and 6 (5.7%)females. Аrterial hypertension stage II has been reported in 100 (95.2%) patients, stage III – 5 (4.8%) patients. Аrterial hypertension 1 degree is established in 74 (70,5%) patients, 2 degrees – 21 (20%), 3 degrees – 10 (9,5%). The average duration of the gout was 4.4 [4; 2] years, arterial hypertension – 5.3 [3; 1] years. Acute gouty arthritis was present in 11 (10.5%) patients, chronic gouty arthritis – 85 (81%), and chronic tofi arthritis – 9 (8.5%). Patients seek medical help from their family doctor too late. Examination of patients with hypertension in combination with gout is not complete, this contributes to underestimation of total cardiovascular risk. In a number of cases, titration of the dose of allopurinol higher than 300 mg is not, performed so only a third of patients reach the target uric acid level.